Phân tích sắc thái nghĩa cầu khiến của các động từ ra lệnh, cấm, cho phép, yêu cầu, đề nghị, khuyên, mời, chúc, xin trogn câu tiếng Việt - Lan, Đào Thanh (VNU Journal of Science: Social Sciences and Humanities, 2004)
Those verbs are performatives verbs which expressing the request and command meaning in the request and command sentence of Vietnamese. Each verb has a difference in request and command level, therefore the way to use one of them is different. Maybe distribute them to : The first level is ra lệnh, cấm, cho phép verbs. Those have strong command meaning, haven’t request meaning. The second level is yêu cầu, để nghị verbs.These have command and request meaning. The command meaning is weaker than the first level. The request meaning of them is the weakest. The third level is khuyên verb. It has command meaning. The command meaning is weaker than the second level. The forth level is mòi verb. It is has the command and request meaning. The command meaning is the weakest. The fifth is chúc verb. It has request meaning and hasn’t command meaning. The request meaning is stronger than the forth level. The sixth level is xin verb. It has request meaning. The request meaning is the strongest.